2011
DOI: 10.1063/1.3660705
|View full text |Cite
|
Sign up to set email alerts
|

Instability of nitrogen doped Sb2Te3 for phase change memory application

Abstract: National Integrate Circuit Research Program of China [2009ZX02023-003]; National Basic Research Program of China [2007CB935400, 2010CB934300, 2011CB309602, 2011CB932800]; National Natural Science Foundation of China [60906004, 60906003, 61006087, 61076121By means of experimental methods and ab initio total energy calculations, we have studied the stability and properties of nitrogen doped Sb2Te3 (NST). The NST film displayed a higher crystallization temperature and sheet resistance than undoped Sb2Te3 (ST) fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…[ 21 ] In addition, the relatively low electrical resistivity of Sb 2 Te 3 , compared with that of GST, leads to large RESET currents and, hence, high switching power. [ 21,22 ] Doping with various elements has, therefore, also been used to try to improve the performance of Sb 2 Te 3 , including dopants, such as C, [ 23 ] N, [ 20 ] O, [ 24 ] Al, [ 25 ] Si, [ 26 ] Ti, [ 27 ] Cr, [ 28 ] Zn, [ 29 ] Ge, [ 30 ] Ag, [ 31 ] Y, [ 32 ] and Sc. [ 33 ] Very recently, a nano‐engineered hetero‐structure, consisting of alternating layers of a few nanometers (3–5 nm) of Sb 2 Te 3 and TiTe 2 , has been shown to exhibit much‐improved PCM behavior, particularly relating to a reduction in time‐dependent resistance “drift” and in electrical noise in the glassy state of the PCM material, Sb 2 Te 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] In addition, the relatively low electrical resistivity of Sb 2 Te 3 , compared with that of GST, leads to large RESET currents and, hence, high switching power. [ 21,22 ] Doping with various elements has, therefore, also been used to try to improve the performance of Sb 2 Te 3 , including dopants, such as C, [ 23 ] N, [ 20 ] O, [ 24 ] Al, [ 25 ] Si, [ 26 ] Ti, [ 27 ] Cr, [ 28 ] Zn, [ 29 ] Ge, [ 30 ] Ag, [ 31 ] Y, [ 32 ] and Sc. [ 33 ] Very recently, a nano‐engineered hetero‐structure, consisting of alternating layers of a few nanometers (3–5 nm) of Sb 2 Te 3 and TiTe 2 , has been shown to exhibit much‐improved PCM behavior, particularly relating to a reduction in time‐dependent resistance “drift” and in electrical noise in the glassy state of the PCM material, Sb 2 Te 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[19] Sb 2 Te 3 also has a very high crystallization speed and, therefore, is a potential candidate material to surpass the data-rate limit imposed by the rate-limiting crystallization process of other PCM materials. [20] However, it also has a low crystallization temperature and, hence, poor thermal stability of the amorphous phase, which is, therefore, detrimental to data retention in the glassy state ("0") at high operating temperatures. [21] In addition, the relatively low electrical resistivity of Sb 2 Te 3 , compared with that of GST, leads to large RESET currents and, hence, high switching power.…”
mentioning
confidence: 99%
“…Experiments have demonstrated that incorporating nitrogen into the PCM is an efficient way to improve the data retention/stability of amorphous states by hindering crystallization. [ 42 ] A similar type of material was utilized in this work, which indicates that our strategies are similar. After setting the initial state of the cell to the amorphous state, a specified M state is created in the doped active layer using a stimulus (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 85%
“…The data show that the formation energy is broadly positive, which means that the incorporation of N is not easy at 0 K, while in practice, this energy might be compensated in the non-equilibrium process with the participation of high energy nitrogen and GST target during the sputtering. 46 In Fig. 2(k), the formation energy of interstitial and vacancy site nitrogen exhibits an overall linear relationship with the doping concentration, indicating that in these configurations N will not interact with each other.…”
Section: Resultsmentioning
confidence: 94%
“…Since the thermal stability of N-dopants has been a concerning topic for nitrogen-doping, 9,46,49 the mean-square displacement (MSD) for nitrogen atoms in various nitrogen-doped polycrystalline cells at different doping levels was calculated, and is shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%